T-fuzzy ideals in BCI-algebras. (18th August 2005) - Akram, M.; Dar, K. H.
Abstract : Using at -normT, we introduce the notions ofT -fuzzy subalgebras andT -fuzzyH -ideals inBCI -algebras and investigate some of their properties.